2023
DOI: 10.1039/d2cp04763b
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study on pseudo Mott phase transition of vanadium dioxide

Abstract: The Peierls geometrical distortion rather than Mott electronic correlation always plays a decisive role in the thermally induced phase transition in which the presence of Coulomb repulsion between electrons does not have an effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In our micromagnetic simulations, K u was tuned in a wide range of 0.5–2 J m −3 in each thickness (Figure 4e), whereas the skyrmionic phase keeps unchanged, meaning that the possible strain‐induced K u variation could not be the substantial reason for the skyrmionic phase transition. On the other hand, a recent study revealed that a 5% compressive strain could lead to a structural transition of Fe 3 GeTe 2 , [ 46 ] which might change the DMI strength. While this strain threshold is an order of magnitude larger than the actual strain in PDMS‐transferred flakes (typically less than 0.22%).…”
Section: Resultsmentioning
confidence: 99%
“…In our micromagnetic simulations, K u was tuned in a wide range of 0.5–2 J m −3 in each thickness (Figure 4e), whereas the skyrmionic phase keeps unchanged, meaning that the possible strain‐induced K u variation could not be the substantial reason for the skyrmionic phase transition. On the other hand, a recent study revealed that a 5% compressive strain could lead to a structural transition of Fe 3 GeTe 2 , [ 46 ] which might change the DMI strength. While this strain threshold is an order of magnitude larger than the actual strain in PDMS‐transferred flakes (typically less than 0.22%).…”
Section: Resultsmentioning
confidence: 99%
“…38 Therefore, for complex multi-structure PT or high-throughput operations, a constant relaxation time ( τ = 10) approximation is usually used. 39…”
Section: Methodsmentioning
confidence: 99%
“…38 Therefore, for complex multi-structure PT or high-throughput operations, a constant relaxation time (t = 10) approximation is usually used. 39 Although dynamical mean-field theory is one of the most useful approaches to strongly correlated electron systems, it is strictly limited and cannot effectively capture the CDW phase transition. 40 So the DFT+U method was finally chosen to use in our calculations.…”
Section: Methodsmentioning
confidence: 99%
“…VO 2 , a typical polycrystalline phase metal oxide, undergoes a reversible transition from an insulating monoclinic phase to a metallic rutile phase at around 68 °C. , In the process of phase transition, the resistance, charge density, spin state, orbital occupancy, and lattice structure of VO 2 all change dramatically . Monoclinic-phase VO 2 has a more distorted structure than rutile-phase VO 2 , whereas rutile-phase VO 2 possesses a narrower energy band gap and a half-full orbital state than monoclinic-phase VO 2 . The different features between the monoclinic phase and rutile phase may give rise to multiple selectivity of VO 2 for different gases.…”
Section: Introductionmentioning
confidence: 99%